2023
DOI: 10.1590/1517-8692202329012022_0279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training on the Anaerobic Capacity of Wrestlers

Abstract: Introduction Since the Wingate anaerobic experiment was proposed in the 1970s, it has come to be used as an important detection method to evaluate athletes’ high-power sport capacity, the effect of training, and the training method. Therefore, it is often used to measure and evaluate the anaerobic work capacity of the human body. Objective Analyze the effects of high-intensity interval training on the anaerobic capacity of male wrestlers. Methods Professional wrestlers from a sports college were selected, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
2
0
1
Order By: Relevance
“…Previously, studies have shown that different forms of SIT can lead to improvements in physiological parameters, specifically VO 2max , peak, and mean power output, in wrestlers (Farzad et al, 2011;Liu and Li, 2023). These findings provide further evidence of the positive impact of SIT on these areas.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previously, studies have shown that different forms of SIT can lead to improvements in physiological parameters, specifically VO 2max , peak, and mean power output, in wrestlers (Farzad et al, 2011;Liu and Li, 2023). These findings provide further evidence of the positive impact of SIT on these areas.…”
Section: Discussionsupporting
confidence: 57%
“…To ensure subjects maintained their maximum effort throughout the entire 30-second duration, verbal encouragement was consistently provided. Peak power output was determined as the highest power achieved at the 5-second mark, while mean power output represented the average power output throughout the entire test (Liu and Li, 2023).…”
Section: Physiological Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Literatür incelendiğinde, sporcuların anaerobik gücü ve başarı durumu arasında güçlü bir ilişkinin olduğu bilinmektedir. 9 Çoğu spor dalı için hayati öneme sahip olan anaerobik güç, kar sporu branşlarında da ön plana çıkmaktadır ve farklı kar sporu branşlarında literatürde anaerobik güçleri ile dikey sıçrama ilişkisini ele alan çalışmaların sınırlılığı nedeniyle bu çalışma önem arz etmektedir. Bu çalışmanın amacı, elit kar branşı sporcularının dikey sıçrama ve anaerobik güç parametrelerinin branşlar arasındaki ilişkisinin incelenmesidir.…”
Section: Anah Tarunclassified